2020
DOI: 10.1007/978-3-030-60376-2_19
|View full text |Cite
|
Sign up to set email alerts
|

The Pi-puck Ecosystem: Hardware and Software Support for the e-puck and e-puck2

Abstract: This paper presents a hardware revision of the Pi-puck extension board that now includes support for the e-puck2. This Raspberry Pi interface for the e-puck robot provides a feature-rich experimentation platform suitable for multi-robot and swarm robotics research. We also present a new expansion board that features a 9-DOF IMU and XBee interface for increased functionality. We detail the revised Pi-puck hardware and software ecosystem, including ROS support that now allows mobile robotics algorithms and utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, in practical situations, the proposed methodology struggles to work efficiently due to the poor quality of the close-range sensors. Furthermore, by employing high-precision sensors, this issue can be rectified to virtually produce any kind of map, as shown in the experiment performed by the authors in [ 36 ]. Ideally, the robots in the swarm should be as simple as possible, and should employ simple algorithms with low overhead, due to practicality.…”
Section: Related Workmentioning
confidence: 99%
“…However, in practical situations, the proposed methodology struggles to work efficiently due to the poor quality of the close-range sensors. Furthermore, by employing high-precision sensors, this issue can be rectified to virtually produce any kind of map, as shown in the experiment performed by the authors in [ 36 ]. Ideally, the robots in the swarm should be as simple as possible, and should employ simple algorithms with low overhead, due to practicality.…”
Section: Related Workmentioning
confidence: 99%
“…According to [85], e-puck 2 is the hardware extension of the e-puck. E-puck 2 is a Raspberry Pi-suitable platform and has high features used by swarm robotics.…”
Section: Mobile Robots Hardware Used For Swarm Roboticsmentioning
confidence: 99%
“…Regarding the information to be gathered, the experiment of Kegeleirs et al (2019) has shown that a robot swarm can produce an occupancy grid of a closed indoor environment in simulation, but struggles in reality because of poor-quality close-range proximity sensors. This means that, provided with the right sensors, a robot swarm can potentially produce any kind of map, as shown by Allen et al (2020) . However, swarm SLAM methods would benefit from low-cost, simple robots that will likely have imprecize sensors.…”
Section: Challengesmentioning
confidence: 99%